Evaluating the impact of perceived information quality on GenAI technology adoption in higher education students (Journal of Applied Learning and Teaching, 2025)
This study investigates the significant influence of perceived information quality (PIQ) on students’ engagement with AI technologies in higher education. Employing structural equation modelling (SEM), we analysed responses from 522 university students to understand how the perceived quality, reliability, and relevance of AI-related information affect their intent and actual usage of generative AI (GenAI). The results reveal that PIQ directly boosts students’ readiness to adopt GenAI, with information frequency serving as a mediator that enhances perceived importance and credibility, thus fostering trust. Additionally, our results show that students who regularly interact with high-quality AI information are more likely to use GenAI tools. However, the presence of information overload can negatively impact actual usage despite high intent to use. These insights offer valuable guidance for educators, policymakers, and tech developers aiming to promote effective adoption of AI tools, thereby improving learning outcomes and student engagement in the digital age.